2014
DOI: 10.1371/journal.pone.0106339
|View full text |Cite
|
Sign up to set email alerts
|

Docking Studies of Pakistani HCV NS3 Helicase: A Possible Antiviral Drug Target

Abstract: The nonstructural protein 3 (NS3) of hepatitis C virus (HCV) helicase is believed to be essential for viral replication and has become an attractive target for the development of antiviral drugs. The study of helicase is useful for elucidating its involvement in positive sense single-stranded RNA virus replication and to serve as templates for the design of novel antiviral drugs. In recent years, several models have been proposed on the conformational change leading to protein movement and RNA unwinding. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 48 publications
(55 reference statements)
3
10
0
1
Order By: Relevance
“…This diterpene interacts with both, the native and the mutated structures of the HCV NS3-4A protease, with a docking score of -15.1 kcal/mol, and this interaction was mediated mainly by the presence of hydrogen bonds between the ligand and S, A and H amino acids in the target protein [5]; in our study, the best interaction between subti1 and HEV capsid protein showed a docking score of -7.0 kcal/mol and was also mediated by the presence of A504 in chain A of the HEV capsid protein, forming two hydrogen bonds ( Table 2). In a similar way, bioflavonoids showed a promissory anti-HCV helicase activity, with high docking scores and with residues D and S as the main amino acids participating in the interaction [13]; these residues were also mediating the interaction of HEV capsid protein and the AVPs designed in our study, suggesting that D and S could be crucial for AVPs interactions ( Table 2). For HCV capsid protein a strongly interaction between naturalderived bioflavonoid has also been demonstrated; in this case, high docking scores according to Molegro Virtual Docker software were probably due to ten H-bonds involving three R residues [29], and in the same way, all the interactions between the six AVPs reported in this study involved R460 in both chains ( Table 2).…”
Section: Discussionsupporting
confidence: 65%
“…This diterpene interacts with both, the native and the mutated structures of the HCV NS3-4A protease, with a docking score of -15.1 kcal/mol, and this interaction was mediated mainly by the presence of hydrogen bonds between the ligand and S, A and H amino acids in the target protein [5]; in our study, the best interaction between subti1 and HEV capsid protein showed a docking score of -7.0 kcal/mol and was also mediated by the presence of A504 in chain A of the HEV capsid protein, forming two hydrogen bonds ( Table 2). In a similar way, bioflavonoids showed a promissory anti-HCV helicase activity, with high docking scores and with residues D and S as the main amino acids participating in the interaction [13]; these residues were also mediating the interaction of HEV capsid protein and the AVPs designed in our study, suggesting that D and S could be crucial for AVPs interactions ( Table 2). For HCV capsid protein a strongly interaction between naturalderived bioflavonoid has also been demonstrated; in this case, high docking scores according to Molegro Virtual Docker software were probably due to ten H-bonds involving three R residues [29], and in the same way, all the interactions between the six AVPs reported in this study involved R460 in both chains ( Table 2).…”
Section: Discussionsupporting
confidence: 65%
“…In addition, in silico analysis revealed that quercetin may be a potential inhibitor of the neuraminidase of influenza A H1N1 and H7N9 viruses [79,80]. Molecular docking analysis also found that quercetin may interact with HCV NS3 helicase, NS5B polymerase and p7 proteins [34,86]. These results correlate with experimental studies showing the anti-HCV activity of quercetin through inhibition of NS3 helicase and heat shock proteins [4,81].…”
Section: Antiviral Activity Of Flavonolssupporting
confidence: 75%
“…Among various compounds, including quercetin, catechins, resveratrol, and lutein, the former two compounds showed good hydrogen bond interactions with best docking energy. These anti-helicase molecules would offer a clue in the development of antiviral drugs [ 96 ].…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 99%